Domestic and Foreign Historiography on Life and Work of V.V.Zenkovsky - Viktoria Poda (Pedagogical Discourse, 2013)
In the article it has been made an attempt to summarize the historiographical material concerning the life and work of Vasyl Vasylovych Zenkovsky. The article deals with the brief review and analysis of the modern Ukrainian and Russian historiography, works on V.V.Zenkovsky published during his lifetime, atheistic Soviet-era historiography; historiography of the Ukrainian diaspora; literature on social, political, historical and philosophical research of the events at the end of the XIX- the beginning of the XX centuries.